2011
DOI: 10.1017/s0025315411001573
|View full text |Cite
|
Sign up to set email alerts
|

Effects of animal size and nutritional status on the RNA/DNA ratio in different tissues of the green-lipped mussel Perna viridis

Abstract: This study aimed to examine the responses of RNA/DNA ratio in Perna viridis under different nutritional status via both field and laboratory studies, and hence evaluate the usefulness of this ratio as a rapid growth biomarker in the mussels. First, the effects of size (small: 30-40 mm; medium: 40-50 mm; large: .50 mm) and tissue type (adductor muscle, foot, gill and hepatopancreas) on the RNA/DNA ratio were investigated in P. viridis collected from three different sites with different degrees of eutrophication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 42 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…In particular, it would inevitably lead to the degradation of RNA that may be contained in food samples, as it has been suggested that in some food products, RNA content is higher than DNA content. For instance, some scientific reports showed that RNA content in seafood could be more than four times the amount in DNA [4,5]. Therefore, RNA losses can cause significant misrepresentation in estimated nutritional value associated with the content of dietNAs in a given food product.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it would inevitably lead to the degradation of RNA that may be contained in food samples, as it has been suggested that in some food products, RNA content is higher than DNA content. For instance, some scientific reports showed that RNA content in seafood could be more than four times the amount in DNA [4,5]. Therefore, RNA losses can cause significant misrepresentation in estimated nutritional value associated with the content of dietNAs in a given food product.…”
Section: Introductionmentioning
confidence: 99%